PERAN MPU KUTURAN DALAM MEMBANGUN PERADABAN BALI (Tinjauan Historis, Kritis) - I NYOMAN SUKA ARDIYASA (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Mpu Kuturan is one of the central figures in building the civilization of Bali, one of which is able to change the order of life of the Balinese towards a better and have a clear order of life. Mpu Kuturan in various texts has many term names such as Senapati Kuturan, De Senapati Kuturan, Sang Senapati Kuturan. However, if viewed from the root he said Mpu Kuturan derived from the word Mpu, Pu, Umpu, Mpukwing used for everyone who has expertise in the field / experts while Kuturan likely comes from the word Kuturan/Kutur which means region. While Senapati is the person in charge of implementing the king's order to his people in development in all fields, including the construction of sacred places. The role of Mpu Kuturan in building Bali is very big, such as the unification of sects in Bali, the establishment of the concept of the village of Pakraman widely known with the concept of Tri Kahyangan, establishing temples of heaven that spread throughout Bali and the most important is to build the order of life of the Balinese pluralists by prioritizing common interests above individual or individual interests. To honor the services of Mpu Kuturan, then made a special pelinggih for him shaped Salwang Manjangan, because the arrival of Mpu Kuturan to Bali supposedly riding a deer.